2019
DOI: 10.1038/s41598-018-37845-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in cardiac structural and tissue characterisation parameters following haemodialysis measured using cardiovascular magnetic resonance

Abstract: In patients with chronic kidney disease (CKD), reverse left ventricular (LV) remodelling, including reduction in LV mass, can be observed following long-term haemodialysis (HD) and has been attributed to regression of LV hypertrophy. However, LV mass can vary in response to changes in myocyte volume, edema, or fibrosis. The aims of this study were to investigate the acute changes in structural (myocardial mass and biventricular volumes) and tissue characterization parameters (native T1 and T2) following HD usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
8
23
0
Order By: Relevance
“…ΔT1 was significantly lower in patients with coronary artery disease; diabetes mellitus compared to patients without these pathologies. Patient who previously had a kidney transplant displayed significantly higher ΔT1 compared to patients who had only been on dialysis found a statistically significant difference, the absolute mean change in native T1 was only 13 ms, representing approximately a 1% change [38].…”
Section: Discussionmentioning
confidence: 83%
“…ΔT1 was significantly lower in patients with coronary artery disease; diabetes mellitus compared to patients without these pathologies. Patient who previously had a kidney transplant displayed significantly higher ΔT1 compared to patients who had only been on dialysis found a statistically significant difference, the absolute mean change in native T1 was only 13 ms, representing approximately a 1% change [38].…”
Section: Discussionmentioning
confidence: 83%
“…Several studies revealed higher native T1 values in CKD patients [ 11 ], whereas more recently, a correlation of native T1 and troponin has also been shown [ 12 ]. A single previous study revealed raised T1 and T2 markers in participants with severe CKD on hemodialysis [ 13 ]. Native T1 of non-scarred myocardium is a strong predictor of survival, CVD mortality and incidence of HF in ischemic and non-ischemic cardiac conditions [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relation between native T1 and markers of adverse LV remodeling in CKD supports the thesis that the mechanism of cardiac dysfunction in CKD is not a consequence of potential ischemic heart disease, but results from the diffuse non-ischemic myocardial changes. The findings from these studies underline also the importance of performing CMR scans at the same timepoint in the weekly dialysis schedule when tracking longer-term changes [40].…”
Section: T1 and T2 Mapping Techniques In Ckdmentioning
confidence: 67%
“…Good correlation between change in indexed LV mass and change in body weight was found. Interestingly, significant improvement in systolic function was observed post-hemodialysis in a group of patients with impaired LV function (LVEF < 45%) [40]. These findings reflect the effect of reduction in myocardial water content following hemodialysis.…”
Section: T1 and T2 Mapping Techniques In Ckdmentioning
confidence: 71%
See 1 more Smart Citation